Factors Related to Safety Climate in Production Line Workers of Food Manufacturing - Yangok, Abdullbasis; Choosong, Thitiworn (International Journal of Engineering and Technology, 2018)
Developing and encouraging a safety culture is an important factor to achieve a safe workplace with low injury rates. Safety climate can be an indicator of the status of an occupational health and safety management system in an organization. It can provide a snapshot of the safety culture. The Thai version of Nordic Occupational Safety Climate Questionnaire is used to evaluate the safety climate in the food manufacturing industry in Songkhla, Thailand. The results can also be used as a guideline in the development and safety management in the future. The response rate was great. The employees who participated were 14.7% male and 85.3% were female. Most subjects were 41-50 years-old and most had a 1- to 5-year working experience. The highest safety climate score of the workers was the dimension of “workers’ trust in the efficacy of safety systems” (3.29) while the lowest score was the dimension of “workers’ safety priority and risk non-acceptance” (2.89). For the leaders, the highest safety climate score was the dimension of “workers’ safety commitment” (3.44) and the lowest score was the dimension of “management safety empowerment” (3.10). The factors related to accident occurrence were the differences in the organizations and the mean score of the safety climate dimension of “worker’s safety priority and risk non-acceptance”.